393. Isavuconazole in the Treatment of Coccidioidal Meningitis. (26th November 2018) - Heidari, Arash; Quinlan, Miriam; Benjamin, David; Mchardy, Ian; Cohen, Stuart H; Johnson, Royce H; Thompson, George R
Abstract: Background: Patients with coccidioidal meningitis require life-long antifungal therapy and cumulative toxicity from these agents may occur. Isavuconazole is the newest triazole antifungal and has demonstrated a lower toxicity profile than voriconazole and may represent a useful therapy in meningitis, although no data regarding efficacy in coccidioidal meningitis has yet been presented. Methods: We conducted a retrospective analysis of all coccidioidal meningitis patients treated at our centers. Data abstracted included demographic and clinical information, results of laboratory and radiographic studies, serologic results, and outcomes. Responses to therapy were measured using a previously validated scoring system used in clinical trials of coccidioidal meningitis (MSG Coccidioidomycosis Scoring System). Results: Nine patients met criteria for inclusion. Seven of nine were previously treated with voriconazole and transitioned to isavuconazole following: photodermatitis, five patients; transaminitis and photodermatitis one patient; failure of therapy, one patient. Two other patients failed fluconazole therapy and were transitioned to isavuconazole as salvage therapy. All patients transitioned to isavuconazole had a complete response to therapy five patients; or were deemed partial response (stable disease), four patients. Conclusion: Isavuconazole therapy resulted in symptomatic and laboratory improvement in five of nine patients. The remaining patients exhibited clinical resolution of symptoms or continued with stable disease following adverse reactions to prior alternative triazole therapy. Isavuconazole may be a useful addition to the therapeutic choices currently available for coccidioidal meningitis. Disclosures: All authors: No reported disclosures.